Influence of Role of Campus-Eatery Regulatory Board on the Production of Safe and Quality Food for Universities of Ilorin Community - Akorede, Seun Nurudeen; Getso, Sanni Ahmed; Abdulfatah, Hajara Aminu; Nofiu, Oluwatobi Daniel; Alapa, John Oyikoicho (NIU Journal of Social Sciences; Vol 4 No 1 (2018): KIU Journal of Social Sciences, Vol. 4 No. 1, March 2018, 2018)
Several health problems may manifest from the food we eat, because of problem that can occur, the food handlers have responsibility to ensure that food provided for consumers are diseases. Several outbreak of food borne illness had happened in campuses and several Nigerian cities. This study examines the role of campus eatery regulatory board on the production of safe and quality food in University of Ilorin. The research design adopted for this study was descriptive research design of survey type. Through a multistage sampling techniques, a sample population of 380 (three hundred and eighty) was selected for the studentâ€™s categories and 130 (one hundred and thirty) was selected from the eatery operatorâ€™s categories in University of Ilorin community. The instrument for the study was two researchers structured questionnaire made up of two sections and a focus group discussion guide. The instrument was later validated by three experts in relevant field and test for reliability with the use of Spearman Brown Order. Using split half method, a reliability of 0.76r was obtained. Personal data collected were analyzed with the use of frequency counts and simply percentage while the postulated hypotheses were tested with the use of inferential statistic of chi-square. Two researcher hypotheses were tested at 0.05 alpha level of significance. All the hypotheses were rejected. The result revealed that: periodic inspection by campus eatery regulatory board influence production of safe               food in university of Ilorin (cal. 2 =355.50> Table value= 16.92 @ DF=9), routine medical screening of eatery operators influence the production of safe food in               University of Ilorin (cal. 2 =301.29> Table value= 16.92 @ DF=9), The study concluded that periodic inspection by C.E.R.B will ensure production of safe foods in the university of Ilorin community, routine medical screening of food handlers will go a long way in influencing production of safe food for the university community, sensitization of food eatery operators will improve eatery operatorsâ€™ knowledge of quality food production. Based on the conclusion drawn, the following recommendation were made: that the university should empower C.E.R.B to embark on more vigorous inspected which may include food test in order to further strengthen the already performing board, C.E.R.B as a matter of importance ensures that all food handlers possess routine medical screening certificate, effective use of customers, complaint hotlines should be encouraged. sensitization on environmental hygiene, personal hygiene and food safety should be doubled, other higher institution of learning should create C.E.R.B in order to forestall food borne diseases outbreak, certified should be issued on a yearly basis to eatery operator after successful inspection.